BRCA1-associated structural variations are a consequence of polymerase theta-mediated end-joining - J. A. Kamp (Nature Portfolio, 2020)
Cancer mutational signatures have been associated with defects in genome maintenance pathways. Here the authors, by using a worm germline mutagenesis model defective of human orthologue BRCA-1, identify polymerase theta-mediated end-joining (TMEJ) as causing the BRCAness mutational signature.